The role of vacancy defects on the dynamic hysteresis properties of ferroelectric thin films: Monte carlo simulation with the DIFFOUR model - Sittidet Srinoi (2018)
In this work, the effect of random vacancy defects on the electrical properties of ferroelectric thin-films was studied. The Monte Carlo simulation, based on the ferroelectric DIFFOUR model, was performed in the lattice system with free and periodic boundary conditions. The Metropolis algorithm was considered in choosing the proper states under the presence of the electric field. From the results, the hysteresis area at a given field was found to depend on the thickness of thin films and the vacancy defects of system. For instance, in thicker films, the larger hysteresis area was observed, which is resulted from the stronger ferroelectric interaction. On the other hand, the hysteresis area decreases with increasing vacancy concentration, due to the reduction of ferroelectric interaction on the average. To understand the hysteresis behaviors, the scaling exponents of associated parameters in the power law scaling form were considered. The results were discussed and compared with these from literatures. Copyright © Taylor &Francis Group, LLC.